The Macroeconomic Influence on the Stock Market: Evidence from a Frontier Market in Asia - Perera, W; Silva, S (Faculty of Humanities and Social Sciences University of Sri Jayewardenepura Nugegoda, Sri Lanka, 2018)
This study evaluates the long and short run influence of the macroeconomic variables on Sri Lankan stock market as a frontier market in Asia. The MSCI Sri Lankan index is used to capture the Sri Lankan stock market. The macroeconomic influence is mainly measured using two domestic macroeconomic variables, four international macroeconomic variables and four global macroeconomic variables. The analysis is based on monthly time series data from 2010 to 2017. The long run influence of macroeconomic variables was examined by employing the Johansen’s co-integration analysis, whilst the short run influence was examined in the light of, autoregressive distributed lag (ARDL) model. The study finds that international and global macroeconomic variables influence on the stock market in Sri Lanka in both long run and the short run, in varying degrees.
Keywords: ARDL; co-integration; macroeconomic variables; frontier market